An urban material flow analysis and carbon footprint assessment of Melaka state - Nor Akmal, Nurhidayah (2023)
Cities are growing at an unprecedented rate, and it will cause several environmental impacts. Relationships between social and ecological systems, cities and their hinterlands, sustainability of resource usage, and social lifestyle in densely populated urban regions are a central focus of this study and field. Thus, material flow analysis (MFA) was used to quantify the material exchanges between the socioeconomic system of a city and its natural surroundings. The study illustrates the material flow of domestic consumption (food, electricity, and water) to depict the input and output of materials in the city of Melaka. MFA improves the understanding of economic systems by pointing to source reduction and the substitution or recycling potential of substances, energy, and materials. Carbon dioxide is the primary greenhouse gas that shows how the climate is changing around the world. Cities are the main part of the carbon emission because of the urbanisation of the city. Thus, the carbon footprint of Melaka is calculated. The study found that the input and output from the MFA is not in the equilibrium state. The output value of food and electricity consumption is larger than its input. Meanwhile, the output value of water consumption is slightly smaller than its input. This was due to eating lifestyles and the high use of electronic devices. The total carbon footprint of Melaka State from electricity and water consumption in 2019 was 28.8 million tCO2 e. By understanding the profile of carbon emissions, it helps in developing strategies for further enhancement of the economic value. The findings in this study show that Melaka citizen needs to practice a low carbon lifestyle to minimise the impact of climate change. This will protect Melaka’s cultural and natural heritage and transform it into a region that is socially and economically stable, attractive to live and work in, and physically resilient to environmental change.